The Effect of Box Breathing in Post Partum Woman - Ni Made Ayu Wulansari; Rinda Intan Sari; Anis Ardiyanti (Indonesian Journal of Global Health Research, 2026)
Factors influencing this include a family history of psychological conditions, childhood trauma, reproductive health factors, and unpleasant experiences during childbirth. Objective: This study aims to determine the effect of box breathing therapy on postpartum mothers. Quasi-experimental pre-post one-group design. This study began with an in-depth exploration of the psychological condition of 55 postpartum mothers. The questionnaire used is the Postpartum Specific Anxiety Scale (PSAS) is validated by Rasch model, alpha coefficient 0,94, unexplained variance values does not exceed 15% and separation item 3.06. The research findings after box breathing showed that 54 respondents experienced a decrease in anxiety scores, while 1 respondent's anxiety score remained constant. 3 respondents were in the anxiety category, and 52 respondents were in the category of not experiencing anxiety. Relaxation therapy with box breathing can be one alternative in managing anxiety in postpartum mothers.